In Vitro Validation of Pulsed Electromagnetic Field (PEMF) as an Effective Countermeasure Against Inflammatory‐Mediated Intervertebral Disc Degeneration - Laura Guarnaccia; Laura Begani; Silvana Pileggi; Mauro Pluderi; Stefano Borsa; Claudia Fanizzi; Massimiliano Domenico Rizzaro; Giorgio Fiore; Laura Fontana; Rolando Campanella; Chiara Cordiglieri; Chiara Gaudino; et al. (JOR Spine)
ABSTRACT Background Intervertebral disc (IVD) degeneration (IDD) is the main contributor to chronic low back pain (LBP), the leading cause of disability worldwide, with a significant impact on the quality of life and health of common people. The etiology of IDD is still unclear, but it has been largely demonstrated the crucial role of inflammation and neuroinflammation in the pathological and degenerative cascade of events characterizing IVD degeneration. Aim In this study, we evaluated the potential therapeutic effect of pulsed electromagnetic field (PEMF) on human degenerated IVD (D‐IVD) cells collected from patients who underwent discectomy. Materials & Methods The experimental plan to test our hypothesis, involved viability assay, reactive oxide species/nitrite production, gene, and protein expression. To recapitulate the pro‐inflammatory disc microenvironment occurring during IDD, interleukin‐1β (IL‐1β) was administered to IVD cell culture. Then, to dissect the contribution of neuroinflammatory condition to immune component, microglial cells were co‐cultured with IVD‐conditioned media, and viability and expression of inflammatory markers were detected. Results Our data prove that in the IVD degenerative microenvironment, the increase of pro‐inflammatory mediators, extracellular matrix degradative enzymes, and neuroinflammatory markers could be reduced by PEMF therapy, resulting in an overall improvement of degenerative condition and LBP. Conclusion These results represent an impactful novelty for the management of people suffering from LPB, in terms of symptom relief and reduction of social‐health system burden.